Multibacillary Leprosy Presenting as Anetoderma in a Young Teenager - Niraj Parajuli; Shraddha Shrestha; Laila Lama; Rushma Shrestha; Sumida Tiwari; Anupama Karki (Hindawi Limited, 2020)
Anetoderma presents as a circumscribed area of slack skin. It can present as either primary or secondary, if associated with other conditions. Leprosy is one of the causes of secondary anetoderma, but it is not commonly reported, especially in multibacillary leprosy. Here, we report a case of a 16-year-old young girl who presented with fever, joint pain, and only three anetodermic plaques. A slit skin smear from the lesion showed multiple acid-fast bacilli with a bacillary index of 3+, thus confirming the diagnosis of leprosy. This case is unique since multibacillary leprosy presented with only few anetoderma lesions in a young teenager girl from a leprosy-eliminated country.